X chromosome-wide association studies in neurological disorders: uncovering the hidden influence of the X chromosome - Step, Kathryn; Leal, Thiago Peixoto; Kamel, Walaa A.; Waldo, Emily; Bardien, Soraya; Mata, Ignacio F. (Frontiers in Genetics, 2025)
X chromosome-wide association studies (XWAS) have identified susceptibility variants for various neurodegenerative and neurodevelopmental diseases. The unique characteristics of the chromosome require more complex analytical approaches than standard genome-wide association studies. Over the past 2 decades, refined XWAS methods have better accounted for this biology. Given that many neurological diseases show sex-biased prevalence, XWAS offers a valuable framework for investigating sex-specific genetic contributions. This review summarizes published neurological XWAS (N = 10), highlighting methodological approaches. Despite the challenges of genetic analyses for the X chromosome, XWAS remains a key approach for studying its role in disease mechanisms.